2000
DOI: 10.1136/thorax.55.1.46
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of systemic cytokine levels in patients with acute respiratory distress syndrome, severe pneumonia, and controls

Abstract: Conclusions-Serum TNF-levels were higher in patients with ARDS than in those with severe pneumonia or in control subjects. Multivariate results suggest that the levels of systemic TNF-and IL-1 reflect the severity of the lung injury rather than the diagnosis. (Thorax 2000;55:46-52)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
99
1
10

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(114 citation statements)
references
References 37 publications
2
99
1
10
Order By: Relevance
“…A cytokine-mediated inflammatory response has been well documented in cases of pneumonia and acute respiratory distress syndrome [5,6,7]. However, few studies have focused on the role of these inflammatory mediators in infection by the Influenza A (H 1 N 1 ) virus [8].…”
Section: Introductionmentioning
confidence: 99%
“…A cytokine-mediated inflammatory response has been well documented in cases of pneumonia and acute respiratory distress syndrome [5,6,7]. However, few studies have focused on the role of these inflammatory mediators in infection by the Influenza A (H 1 N 1 ) virus [8].…”
Section: Introductionmentioning
confidence: 99%
“…Others, such as Hyers have found variability in the elevation of TNF-, however, there is speculation that TNF-is an acute phase cytokine and the timing of studies is important for its evaluation (Hyers, 1991). Although Bauer found that the TNF-levels were significantly elevated it was also speculated that the elevation was more related to the severity of the lung disease and could not be extrapolated as a possible diagnostic marker for ARDS (Bauer et al, 2000). TNF-is a known acute phase reactant and is also a cytokine involved in systemic inflammation.…”
Section: Serum Biomarkers In Permeability Edema and Ardsmentioning
confidence: 99%
“…The cytokine, TNFinduces macrophages and T H 1 cells and activates ECs and macrophages (Braun et al, 2005). Studies have been conflicting as far as elevation of TNF-in patients with ARDS pulmonary edema, for example, Bauer demonstrated that TNF-concentrations were significantly higher in patients with ARDS than those of pneumonia or of the control subjects (Bauer et al, 2000). Others, such as Hyers have found variability in the elevation of TNF-, however, there is speculation that TNF-is an acute phase cytokine and the timing of studies is important for its evaluation (Hyers, 1991).…”
Section: Serum Biomarkers In Permeability Edema and Ardsmentioning
confidence: 99%
See 1 more Smart Citation
“…The systemic level of IL-1β seems to reflect the severity of the lung injury rather than the diagnosis in different lung diseases 70 . The levels of IL-1β in BAL fluid from patients with ARDS did not differ between survivors and non-survivors, but low concentrations of anti-inflammatory cytokines IL-1Ra and IL-10 were associated with worse prognosis 68 .…”
Section: Lungmentioning
confidence: 99%